THE VIRTUOUS CITIZEN: REGIMES AND AUDIENCES - Iovan DREHE DREHE (Studia Universitatis Babeș-Bolyai. Philosophia)
The purpose of the present paper is to sketch the possibility of an audience theory specific to virtue argumentation taking as a starting point what Aristotle has to say about political audiences in the context of specific political constitutions and building on insights offered by the New Rhetoric argumentation theory of Chaïm Perelman and Lucie Olbrechts-Tyteca and the responsibilist virtue epistemology of Linda Trinkaus Zagzebski.